Hubungan asupan gizi seimbang, pola asuh dengan perkembangan motorik balita gizi kurang di Kota Jambi - dian octavia (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2017)
AbstractBackground: Most cases of growth failure (malnutrition) occur due to inadequate food consumption in terms of number and type. Lack of food intake is most often caused by psychosocial problems, including lack of access to food, ignorance, and misperceptions of parents about proper food, environmental dysfunction or eating interactions, and more global parent-child relationship issues.Methodology Research: This research is a quantitative research with a cross-sectional design that aims to determine the relationship between balanced nutrition intake and parenting patterns against motor development less nutrition. The population in this study were mothers who had under-five children with less nutrition recorded in Payo Selincah Community Health Center, Simpang IV Sipin Public Health Center, Handil Health Center, Paal V Public Health Center of Jambi City in 2016. The number of samples in this study amounted to 48 samples. The technique of taking place of research using Multistage Random Sampling. The sample selection technique is purposive sampling. Data analysis tested is univariate-bivariate analysis using chi-square statistic test.Results: The results showed that there was a significant relationship between balanced nutritional intake (p-value = 0,017) to motor development of under-fives malnutrition. There is no significant correlation between parenting pattern (p-value = 0,093) to motor development in underweight children less.Conclusion: It is expected that parents pay more attention to nutrition intake in children under the age of five. As a nutritional balanced in accordance with the needs of children's growth will give a big influence on growth development of children. It is expected health workers, especially in primary health center officers to always remind parents to provide balanced nutrition for children under five.